2015
DOI: 10.1039/c4ra12118j
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic cell responses and antibacterial efficacy of Cu/Zn co-substituted hydroxyapatite coatings on pure titanium using electrodeposition method

Abstract: Effective physiological bone integration and absence of bacterial infection are essential for a successful orthopaedic or dental implant. This work elucidated the antibacterial efficacy and cytocompatibility of electroplated Cu(II) and Zn(II) co-substituted hydroxyapatite (HAP) (i.e., ZnCuHAP) coating on commercially pure titanium (Ti-cp). To improve the antibacterial property of pure HAP, Cu 2+ was substituted into its structure.Simultaneously, Zn 2+ is co-substituted as secondary material into CuHAP to offse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…The produced systems include the co-substitution of zinc/silver [209], silver/strontium [211], carbonate/strontium [492], carbonate/magnesium [454,493], carbonate/sodium [494], carbonate/silicate [495], yttrium/silicon [496], zinc/silicate [497], zinc/copper [498], strontium/cerium [499], magnesium/ strontium [500], magnesium/silver [501], and carbonate/silicate/magnesium [454]. However, the co-substitution of multiple (more than two) ions has not deeply and systematically attempted and investigated, and thus, it can be considered as a promising research field to be still and further explored and expanded [502,480].…”
Section: Discussionmentioning
confidence: 99%
“…The produced systems include the co-substitution of zinc/silver [209], silver/strontium [211], carbonate/strontium [492], carbonate/magnesium [454,493], carbonate/sodium [494], carbonate/silicate [495], yttrium/silicon [496], zinc/silicate [497], zinc/copper [498], strontium/cerium [499], magnesium/ strontium [500], magnesium/silver [501], and carbonate/silicate/magnesium [454]. However, the co-substitution of multiple (more than two) ions has not deeply and systematically attempted and investigated, and thus, it can be considered as a promising research field to be still and further explored and expanded [502,480].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are controversies concerning the effects of Zn on osseointegration and biocompatibility. On the one hand, Zn surfaces increase initial adhesion, spreading activity, alkaline phosphatase activity, collagen secretion and extracellular matrix mineralization of eukaryotic cells 6,108,129,164) . On the other hand, they exhibit dosedependent negative effects on cell proliferation, cell morphology, osteogenic gene expression and cell viability of eukaryotic cells 135) .…”
Section: Anodically Oxidized/ Ion-implanted Surfacesmentioning
confidence: 99%
“…Zn incorporation into implants was shown to stimulate bone formation around the implant and reduce inflammatory response [17]. Recent studies have shown that Zn-doped HA coating can release trace Zn 2+ in the degradation process, which is favourable to improve cell proliferation [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of biological and physicochemical properties of HA can be achieved by doping with ions that are usually present in natural apatites of vertebrate skeletal systems [8]. A wide variety of anions, cations and functional groups, such as Na + [9], Sr 2+ [10], Zn 2+ [11], Mn 2+ [12], SiO 4 4− [13], F − [14], Cl − [15], and CO 3 2− [16], can be introduced into the single phase HA lattice. Amongst these substitutions, zinc and fluorine are widely considered as potential substituents because of their biological relevance [17].…”
Section: Introductionmentioning
confidence: 99%